1994
DOI: 10.1101/gad.8.21.2629
|View full text |Cite
|
Sign up to set email alerts
|

Efficient translation of poly(A)-deficient mRNAs in Saccharomyces cerevisiae.

Abstract: The polyadenylate tail of eukaryotic mRNAs is thought to influence various metabolic phenomena including mRNA stability^ translation initiation, and nucleo-cytoplasmic transport. We have analyzed the fate of mRNAs following inactivation of poly(A) polymerase in Saccharomyces cerevisiae containing a temperature-sensitive, lethal mutation {papl-1) in the gene for poly (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
42
1

Year Published

1995
1995
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(45 citation statements)
references
References 45 publications
2
42
1
Order By: Relevance
“…Comparisons of mRNA levels, enzyme assays, and analyses of mRNA association with polyribosomes demonstrated that translation of the TRP4-ribozyme mRNA was reduced approximately 50-75%+ Impaired utilization of this mRNA may well reflect the important role of the poly(A) tail in translation initiation (Munroe & Jacobson, 1990;Tarun & Sachs, 1995;)+ Under most circumstances, it would be expected that a poly(A)-deficient mRNA would initiate poorly in yeast (Gallie, 1991;Proweller & Butler, 1994), an event consistent with the shift of approximately half of the ribozymecontaining mRNA to the nonpolysomal fractions of the cytoplasm (Fig+ 3)+ It is likely that the TRP4-ribozyme construct used here will prove valuable in further analyses of the mechanism of translation of poly(A) Ϫ mRNAs in yeast+ An additional translational regulatory phenomenon uncovered by these studies is suggested by the specific translational activity of the TRP4 ⌬39 UTR mRNA (Fig+ 2)+ Whereas the level of this mRNA is reduced more than threefold, relative to wild-type, PR-transferase activity is reduced less than half+ These results imply that the deletion has removed a TRP4 39 UTR sequence element normally capable of repressing translation of this mRNA+ The existence of such an element is not without precedent (Gray & Wickens, 1998)+ As summarized above, cells expressing the TRP4-ribozyme construct have decreased levels of Trp4p and are starved for tryptophan+ In light of the ability of yeast cells to alter their patterns of gene expression to ensure survival in different environments, it was not surprising that the TRP4-ribozyme construct elicited the activation of the general control system of amino acid biosynthesis+ The partial activation observed undoubtedly reflects the ability of cells harboring these constructs to synthesize modest amounts of tryptophan sufficient to support growth of trp4 cells+…”
Section: Discussionmentioning
confidence: 99%
“…Comparisons of mRNA levels, enzyme assays, and analyses of mRNA association with polyribosomes demonstrated that translation of the TRP4-ribozyme mRNA was reduced approximately 50-75%+ Impaired utilization of this mRNA may well reflect the important role of the poly(A) tail in translation initiation (Munroe & Jacobson, 1990;Tarun & Sachs, 1995;)+ Under most circumstances, it would be expected that a poly(A)-deficient mRNA would initiate poorly in yeast (Gallie, 1991;Proweller & Butler, 1994), an event consistent with the shift of approximately half of the ribozymecontaining mRNA to the nonpolysomal fractions of the cytoplasm (Fig+ 3)+ It is likely that the TRP4-ribozyme construct used here will prove valuable in further analyses of the mechanism of translation of poly(A) Ϫ mRNAs in yeast+ An additional translational regulatory phenomenon uncovered by these studies is suggested by the specific translational activity of the TRP4 ⌬39 UTR mRNA (Fig+ 2)+ Whereas the level of this mRNA is reduced more than threefold, relative to wild-type, PR-transferase activity is reduced less than half+ These results imply that the deletion has removed a TRP4 39 UTR sequence element normally capable of repressing translation of this mRNA+ The existence of such an element is not without precedent (Gray & Wickens, 1998)+ As summarized above, cells expressing the TRP4-ribozyme construct have decreased levels of Trp4p and are starved for tryptophan+ In light of the ability of yeast cells to alter their patterns of gene expression to ensure survival in different environments, it was not surprising that the TRP4-ribozyme construct elicited the activation of the general control system of amino acid biosynthesis+ The partial activation observed undoubtedly reflects the ability of cells harboring these constructs to synthesize modest amounts of tryptophan sufficient to support growth of trp4 cells+…”
Section: Discussionmentioning
confidence: 99%
“…41). We showed previously that, at 35°C in a pap1-1 background, PAB1 mRNA exists without detectable poly(A) tails, while PGK1 mRNA exists as a mixture of mostly poly(A)-deficient and poly(A) ϩ species as determined by oligo(dT) cellulose selection (31) . Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Our laboratory recently showed that yeast cells with a conditional mutation (pap1-1) in the poly(A) polymerase gene accumulated poly(A)-deficient and poly(A) Ϫ mRNA following inactivation of the enzyme by cell growth at a nonpermissive temperature (35°C) (31). A 1-h incubation at 35°C reduced the total amount of mRNA approximately 2-fold, consistent with an important role for poly(A) tails in mRNA stability.…”
mentioning
confidence: 89%
See 1 more Smart Citation
“…The effects are often small in in vitro translation systems, but more pronounced differences have been seen in experiments where mRNAs were microinjected into Xenopus oocytes [343] or electroporated into cells 13441 (see, however, [345] which describes rather different behaviour in yeast). In the reticulocyte lysate, a rather small increment in efficiency of recruitment of poly(A)-bearing mRNA was localized to the joining of the 60s ribosomal subunit to the 43s .…”
Section: General Role Of Poly(a) and Pabp In Translationmentioning
confidence: 99%